Hubungan Antara Nyeri Punggung Bawah Terhadap Keseimbangan Dinamis Pada Ibu Hamil Trimester II Dan III Di Puskesmas Kecamatan Duren Sawit - Salisiyah Mardiyatun Jihada; Zulfikar H Wada; Robiatun Amalia Ranti (JURNAL ILMIAH NUSANTARA, 2024)
Low back pain in pregnancy is the most common symptom affecting 24% to 90% of women worldwide. Lower back pain will cause a decrease in the flexibility of core muscles such as the erector spine, external obliques and gluteus maximus, resulting in changes in posture and causing a decrease in balance in pregnant women. In addition, decreased postural stability in pregnant women with low back pain will affect the risk of falls. In pregnant women, it was found that around 27% of the risk of falls was due to balance disorders. The aim of this research is to determine the relationship between lower back pain and dynamic balance in pregnant women at the Duren Sawit Community Health Center. Cross Sectional is the method in this research with a correlation approach. The population in this study were pregnant women in the second and third trimesters at the Duren Sawit District Health Center, East Jakarta. The number of samples in this study was 77 pregnant women. In this study, 2 instruments were used, namely the Visual Analog Scale (VAS) to measure the intensity of low back pain and the Timed Up and Go Test to measure dynamic balance. Based on the results of the correlation analysis that has been carried out, the relationship between lower back pain and dynamic balance shows that the correlation results are significant P = < 0.001.